Seguimiento del consumo del suplemento alimentario para madres lactantes de Salinas, Simiatug y Guanujo. Octubre 2024 – enero 2025. - Mariño Meneses, Jeimy Estefanía (2025)
Maternal and child health is essential for adequate nutritional status, especially in rural areas with diminished access to health and nutrition services. Food supplementation for lactating mothers is necessary to ensure the well-being of mothers and infants. This research evaluates adherence and different effects of food supplementation on the health of lactating mothers in Salinas, Simiatug and Guanujo. Objective: To determine the consumption of food supplementation for nursing mothers in Salinas, Simiatug and Guanujo in the period from October 2024 to January 2025. Methodology: Applied and quasi-experimental study, using a quantitative, descriptive and cross-sectional approach. Eighteen lactating mothers were surveyed to collect sociodemographic, dietary and adherence data to the supplement and to evaluate its nutritional impact. Results: Mothers showed variable adherence to the supplement. In Guanujo, the majority improved their nutritional status from overweight to normal weight. In Salinas, the majority maintained their normal weight since pregnancy, with a minority being overweight. In Simiatug, overweight cases increased, indicating the need for specific interventions. Conclusion: It is essential to implement training strategies and nutrition education programs that address barriers and promote consistent adherence to dietary supplementation, considering individual and contextual factors.